Proanthocyanidin-rich date seed extract protects against chemically induced hepatorenal toxicity - Ahmed, Atallah F.; Al-Qahtani, Jawaher H.; Al-Yousef, Hanan M.; Al-Said, Mansour S.; Ashour, Abdelkader Elbadawy Abbas; Al-Sohaibani, Mohammed; Rafatullah, Syed (Mary Ann Liebert, Inc, 2015)
A hydroacetone extract was prepared from seeds of Phoenix dactylifera L. var. Khalas, which is an industrial by-product of date processing. The proanthocyanidin nature of the extract (coded as DTX) was characterized by phytochemical and nuclear magnetic resonance (NMR) analyses. The total phenol/proanthocyanidin content and antioxidant activity of DTX were estimated by Folin-Ciocalteu, vanillin-sulfuric acid, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays, respectively. The hepatorenal protective activity of DTX was evaluated using CCl4-induced toxicity model in rats, in comparison with silymarin (SYL). Results of the histopathological examination and measurements of various hepatorenal serum indices and tissue biochemical markers demonstrated that DTX displayed marked protective potential against CCl4-induced liver and kidney injury at 100 mg/kg/rat. Relative to the control CCl4-intoxicated group, pretreatment with DTX significantly (P<.001) suppressed the elevated serum levels of alanine aminotransferase and aspartate aminotransferase (ALT and AST), alkaline phosphatase (ALP), γ-glutamyl transferase (GGT), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), bilirubin, creatinine, and calcium, whereas it significantly (P<.001) increased the diminished serum levels of high-density lipoprotein cholesterol (HDL-C) and total protein (TP). Moreover, DTX significantly decreased malondialdehyde (MDA) formation and increased TP synthesis in hepatorenal tissues compared with the intoxicated control. The improvement in biochemical parameters by DTX was observed in a dose-dependent manner and confirmed by restoration of normal histological features. The acute toxicity test of DTX in rats revealed safety of the extract. This study reveals that DTX enhances the recovery from xenobiotics-induced toxicity initiated by free radicals.